Machine Learning or Human Education? Thoughts and Data on Artificial Intelligence and the Labor Market: Economic Sociological Aspects of Career Orientation. - Keszi, Roland (Fogyatékosság és Társadalom)
The economic trends reviewed in this paper will play a prominent role in the labor market of the near future with the exponential growth of the uptake of artificial intelligence applications. The author reviews some of the megatrends related to the economic and social aspects of artificial intelligence from the demand side of the labor market, based on recent macroeconomic data sources, empirical research and forecasts. The main approach of the study is a secondary analysis of macroeconomic and survey sociological data based on a synthesis of literature reviews. The only exception to this methodological approach is a simple combination of network analysis and natural language processing (NLP) in the first part of the study, which is based entirely on the author’s own web scraping-based data collection and calculations. The trends under review directly affect the employees of the present day and are currently prominent in companies’ recruitment processes, i.e. they should be seen as an intensely present pattern on the demand side of the labor market. Some dangerous labor market and economic sociological megatrends are also reviewed in the paper. The author also draws attention to some of the striking trends that are expected in connection with the transformation of occupational structures and labor market polarization. The article reviews – from the demand side of the labor market – the skills and competences that are expected to increase and to which career guidance practitioners should pay particular attention in the coming years.